PRELIMINARY EVALUATION OF AQUIFER STORAGE AND RECOVERY IN THE RECIFE METROPOLITAN REGION, PERNAMBUCO, BRAZIL - Leite, Betty T. (Águas Subterrâneas, 2000)
The water shortage problem in northeastern Brazil has challenged local water suppliers over the years. Groundwater development in areas with adequate hydrogeology has been intensively used to supplement water demands. As a result, underground resources are subject to adverse environmental impacts associated with overdraft conditions. The city of Recife is a good example of an area the extensive decline in groundwater levels has brought up the concerns for potential impacts such as salt water intrusion and subsidence. This paper provides a preliminary evaluation of the applicability of Aquifer Storage and Recovery (ASR) in the Recife Metropolitan Region (RMR). ASR is an environmentally-friendly water supply alternative that helps meet water demand needs and plays an important role in resolving several water resource and environmental issues. This preliminary investigation points out ASR benefits for the area, identifies issues affecting operations, and recommends steps to be taken to demonstrate the feasibility of ASR for the RMR. Based on the extent of the available data, an ASR program appears feasible in the RMR as a tool to mitigate water shortage conditions, declined water levels, salt water intrusion and potential subsidence within the coastal aquifers.